The "Panjang Jimat" Tradition of Kasepuhan Cirebon in Strengthening National Identity - Ardi Afriansyah; Wiwin Widia Sari; Trisna Sukmayadi (Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The city of Cirebon has a wealth of valuable traditions and cultural heritage, especially the tradition of Panjang Jimatan in Kasepuhan Palace. However, globalization and modernization threaten the preservation of this tradition. This research aims to understand the essence of the Panjang Jimatan tradition as part of Indonesia's national identity and find strategies for its preservation in the modern era. Through a qualitative and case study approach, this research uses observation, interviews, and documentation for data collection. The informants involved include traditional leaders, community organizations, and local communities. The results show that the Panjang Jimatan tradition is a religious ritual and reflects deep cultural, historical, and spiritual values. The values and symbolism in this tradition emphasize respect for the Prophet Muhammad and the spirit of mutual cooperation in the community. The new findings of this research show that the community's active involvement and the government's support are very important in preserving this tradition. This research contributes to providing new insights into cultural tradition preservation strategies as part of efforts to strengthen national identity and maintain traditional cultural heritage in Indonesia.